AB0766 Bakers' Cyst and Tibiofemoral Abnormalities Are More Distinctive MRI Features of Symptomatic Osteoarthritis than Patellofemoral Abnormalities. (15th July 2016) - Visser, W.; Mertens, B.; Reijnierse, M.; Bloem, J.L.; de Mutsert, R.; le Cessie, S.; Rosendaal, F.R.; Kloppenburg, M.
Abstract : Background: In knee osteoarthritis (OA) structural abnormalities can be present in all joint tissues and compartments. These abnormalities are not OA specific and co-occur in different joint locations. Which structural abnormalities can identify symptomatic OA is unclear. Objectives: We investigated magnetic resonance (MR) abnormalities in the knee that can discriminate best between individuals with and without symptomatic OA. Methods: The Netherlands Epidemiology of Obesity (NEO) study is a population-based cohort including 6671 individuals aged 45–65 years, of which 1284 participated in a MR imaging sub-study. Structural abnormalities (osteophytes, cartilage loss, bone marrow lesions (BMLs), subchondral cysts, meniscal abnormalities, effusion, Baker's cyst) at 9 patellofemoral and tibiofemoral locations were scored using the knee OA scoring system. Symptomatic OA in the imaged knee was defined following the ACR criteria. The relation between structural abnormalities on different locations within the joint was visualized by network graphs, constructed using R, by estimating a sparse inverse covariance matrix using a lasso penalty, based on the pooled variance-covariance matrix across the entire study population. Logistic ridge regression analyses using a double cross-validatory approach were used to investigate which MR abnormalities discriminate best between individuals with and without symptomatic OA, taking co-occurrence of all abnormalities into account. Higher regression coefficients reflect better discrimination between presence or absence of symptomatic OA. Analyses were performed crude and adjusted for age, sex and BMI. Results: In the sub-study (55% women, median age 56 years (IQR 50–61), BMI 30.0 kg/m 2 (27.9–33.0)) 177 participants had symptomatic knee OA. All MR abnormalities except for subchondral cysts were highly frequent both in individuals with and without OA. The network graphs showed relations between osteophytes within all compartments of the knee and between cartilage defects on different locations. Within the same compartment, osteophytes and cartilage defects were related. Baker's cysts showed the highest regression coefficient (0.293) for presence of symptomatic OA, followed by osteophytes and BMLs in the medial tibiofemoral compartment (0.185–0.279), osteophytes in the medial trochlear facet (0.262), and effusion (0.197). After adjustment for age, sex and BMI, the same abnormalities identified OA best. The area under the curve of the logistic ridge regression model including all assessed abnormalities was approximately 0.7. The figure illustrates which abnormalities best identify symptomatic OA (A: Baker's cyst, effusion, osteophyte in medial trochlear facet, B: osteophytes in medial femoral condyle and medial tibial plateau, C: BMLs in medial femoral condyle and medial tibial plateau). Conclusions: Baker's cysts discriminate best between individuals with and without symptomatic knee OA. Especially structural abnormalities as osteophytes and BMLs in the medial side of the tibiofemoral joint and effusion add further in discriminating symptomatic OA. Presence of Baker's cysts may present as a target for treatment. Disclosure of Interest: None declared